Digital media and impulse consumption by the millennial generation in retail - Bances Sánchez, Jorge Iván; Panta Merino, Mónica Esther; Valderrama Puscan, Marlon Walter (LACCEI, 2025)
Currently, impulse consumption in the millennial generation, the mechanisms that underlie such consumption in a particular cultural environment are not well understood, nor is the perception of guilt and the tendency to spend of this population. The study is related to two of the Sustainable Development Goals (SDGs): goal 12 related to responsible consumption and production is relevant, as it seeks to promote sustainable and efficient consumption patterns; followed by SDG 8, which seeks the realization of decent work and economic growth. The purpose of the research was to determine the relationship between digital media and impulse consumption of the millennial generation in a retail store. Its methodology included a basic type of study, descriptive approach, non-experimental - cross-sectional design, a study sample of 248 customers was considered and the survey was used as a data collection technique. In relation to the results, a low significant relationship was obtained between the use of digital media and impulsive consumption in the millennial generation, concluding that digital media influence the impulsive consumption of the millennial generation, however, this effect is relatively weak.